A New Vitality in General Education. Planning, Teaching, and Supporting Effective Liberal Learning by the Task Group on General Education - Association of American Colleges, Washington, DC.; Association of American Colleges, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1988)
The rationale, purposes, and scope of general education are considered, along with issues of implementation, and specifically effective ways of planning programs and courses, teaching them, and supporting them. Examples of good educational practice are provided, as well as suggestions for future improvements. A section on planning effective general education considers content, essential skills, creating new courses and programs, and integrating content and inquiry. A new definition of teaching is offered, and attention is directed to active learning, assessing student progress, and enlisting students as coinquirers. The following topics concerning institutional support are addressed: changing the environment, integrating commuter students, improving residential life, expanding cross-cultural experiences, creating cross-disciplinary seminars, organizing campus think tanks, assessing programs, assuring administrative support, and revitalizing general education. (SW)
Availability: Association of American Colleges, 1818 R Street, NW, Washington, DC 20009 ($7.00 single copy; 20-100 copies, $5.00 per copy; 100 or more, $4.00 per copy; prepaid).
Sponsoring Agency: Johnson Foundation, Inc., Racine, WI.
Sponsoring Agency: EXXON Education Foundation, New York, NY.
Microfiche.
Keywords: Advisory Committees